2009
DOI: 10.1007/s10571-009-9481-4
|View full text |Cite
|
Sign up to set email alerts
|

Pilocarpine-Induced Seizures Produce Alterations on Choline Acetyltransferase and Acetylcholinesterase Activities and Deficit Memory in Rats

Abstract: In the present study, we investigated the effect of seizures on rat performance in the Morris water maze task, as well as on choline acetyltransferase (ChAT) and acetylcholinesterase (AChE) activities in rat hippocampus. Wistar rats were treated with 0.9% saline (i.p., control group) and pilocarpine (400 mg/kg, i.p., pilocarpine group). After the treatments all groups were observed for 1 h. The changes on reference and working spatial memory caused by pilocarpine administration were observed in seized rats. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…O'Donnell et al (2010) stated that the inhibition of AchE leads to a build-up of extracellular ACh and a series of toxic consequences including hypersecretion, tremor, convulsion/ seizure,coma, and death. In addition, the findings of de Sales et al (2010) reported that seizures caused a decrease in AChE activity, expecting that the constant inhibition of this enzyme by seizures might increase ACh levels. In addition to the antioxidant effect of N. sativa, oil and thymoquinone have been demonstrated to prevent oxidative injury during cerebral ischemia-reperfusion injury in rat (Hosseinzadeha et al, 2007) and in a rat model of subarachnoid hemorrhage (Ersahin et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…O'Donnell et al (2010) stated that the inhibition of AchE leads to a build-up of extracellular ACh and a series of toxic consequences including hypersecretion, tremor, convulsion/ seizure,coma, and death. In addition, the findings of de Sales et al (2010) reported that seizures caused a decrease in AChE activity, expecting that the constant inhibition of this enzyme by seizures might increase ACh levels. In addition to the antioxidant effect of N. sativa, oil and thymoquinone have been demonstrated to prevent oxidative injury during cerebral ischemia-reperfusion injury in rat (Hosseinzadeha et al, 2007) and in a rat model of subarachnoid hemorrhage (Ersahin et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…67 Inhibition of AChE activity is associated with the accumulation of acetylcholine resulting in the development of neurological consequences including convulsions and tremors. 68 Monoamines are known to play an essential role in the development of epileptogenesis. The deficiency of monoamines was found to promote neuronal hyperexcitability in human and animal studies.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, AChE alters neuronal excitability, promotes synaptic plasticity, and modulates memory and neuronal functions [72]. The deactivation of AChE is linked with the accumulation of acetylcholine at the synapse, resulting in the progression of convulsions [73]. Interestingly, it was evident that the treated mice with EGCG-SeNPs could restore all the changes in the neuronal biomarkers and neurotransmitter levels to their normal ranges compared to the control and PTZ-exposed groups.…”
Section: Discussionmentioning
confidence: 99%